1988
DOI: 10.1042/bst0160620
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dietary mutagen activation by methylxanthines

Abstract: 1970) J. Rid. C'hem. 245,6649-6656 Kes. Comrnun. 24, 79-84 ( 1 986) Insect Hiochem. 16,749-756 Vol. I6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Both are known to be substrates for cytochrome P450 IA2-mediated reactions, as are aromatic and heterocyclic amines (19,20). Caffeine has been reported to inhibit the mutagenicity of various heterocyclic amines in Salmonella (15,21,22) However, analysis of urine extracts by HPLC revealed that the concentrations of these methylxanthines in urinary extracts were far too low to account for their inhibitory effect on PhIP mutagenicity, as reported previously (3). An inhibitory effect of unsaturated fatty acids on the mutagenicity of heterocyclic amines and other carcinogens has been reported (23) and their presence in human urine is well documented (24).…”
Section: Discussionmentioning
confidence: 83%
“…Both are known to be substrates for cytochrome P450 IA2-mediated reactions, as are aromatic and heterocyclic amines (19,20). Caffeine has been reported to inhibit the mutagenicity of various heterocyclic amines in Salmonella (15,21,22) However, analysis of urine extracts by HPLC revealed that the concentrations of these methylxanthines in urinary extracts were far too low to account for their inhibitory effect on PhIP mutagenicity, as reported previously (3). An inhibitory effect of unsaturated fatty acids on the mutagenicity of heterocyclic amines and other carcinogens has been reported (23) and their presence in human urine is well documented (24).…”
Section: Discussionmentioning
confidence: 83%
“…We previously demonstrated that macro-and microcomponents of the diet such as fat, fiber, and plant flavonoids can modify the in vivo genotoxicity of heterocyclic amines by altering their uptake from the gut lumen or their metabolism (12)(13)(14)(15). Another microcomponent of the Western diet, caffeine, has been shown by us and others to inhibit the in vitro conversion of heterocyclic amines to genotoxins (16,17). Caffeine is of particular interest, because its own metabolism is, like MelQx, to some degree dependent on CYP1A2 (18).…”
Section: Introductionmentioning
confidence: 96%
“…The biological monitoring of Trp-P-1 and Trp-P-2 in human plasma , and MeIQx in human urine (Murray et al 1989) show that humans are widely exposed to measurable quantities of these compounds. The fact that microsomal fractions of human liver can convert both MeIQx (Murray et al 1988) and 2-amino-l-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) (McManus et al 1989) to potent mutagens in the Ames Salmonella test, and the fact that N-acetylated metabolic products of Glu-P-1 and Glu-P-2 have been found in human urine, bile, liver and kidney (Kanai et al 1988) indicate that these compounds may be suspect human carcinogens. However, until more information is obtained about the carcinogenicity of these compounds in dose-response studies, including low exposures, and in animal species other than rats and mice, in which their potency is only moderate, and more comprehensive information on their occurrence in foods is available, the potential human cancer risk presented by these compounds will be hard to evaluate.…”
Section: Heterocyclic a M I N E S ( P R O T E I Y Pyrolysis P R O D Umentioning
confidence: 99%